You need to open the brackets such that:

`e^x*(1-cos e^x) = e^x - e^x*cos e^x`

Integrating both sides yields:

`int e^x*(1-cos e^x) dx= int e^x dx- int e^x*cos e^x dx`

`int e^x*(1-cos e^x) dx = e^x - int e^x*cos e^x dx`

You need to solve the integral `int e^x*cos e^x dx` , hence you should come up with the notation `e^x = y =gt e^x dx = dy`

You need to write `int e^x*cos e^x dx` in terms of y such that:

`int e^x*cos e^x dx = int cos ydy = sin y + c`

You need to substitute`e^x` for y such that:

`int e^x*cos e^x dx = sin e^x +` c

`int e^x*(1-cos e^x) dx = e^x - sin e^x + c`

**Hence, evaluating the integral of function `e^x*(1-cos e^x) ` yields `int e^x*(1-cos e^x) dx = e^x - sin e^x + c` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now